Mitochondrial 13513G>A Mutation With Low Mutant Load Presenting as Isolated Leber's Hereditary Optic Neuropathy Assessed by Next Generation Sequencing - Sun, Chuan-bin; Bai, Hai-xia; Xu, Dan-ni; Xiao, Qing; Liu, Zhe (Frontiers in Neurology, 2021)
Objective: Mitochondrial 13513G>A mutation presenting as isolated Leber’s hereditary optic neuropathy (LHON) without any extraocular pathology has not been reported in literature. We herein evaluate the clinical characteristics and heteroplasmy of m.13513G>A mutation manifesting as isolated LHON. Methods: Seven members of a Chinese family were enrolled in this study. All subjects underwent detailed systemic and ophthalmic examinations. Mitochondrial DNA in their blood was assessed by targeted PCR amplifications, next generation sequencing (NGS), and pyrosequencing. One hundred of blood samples from ethnic-matched healthy volunteers were tested by NGS and pyrosequencing as normal controls. Results: Isolated LHON without any other ocular or extraocular pathology was identified in a 16 year old patient in this family. Heteroplasmic m.13513G>A mutation was detected by NGS of the full mtDNA genome in the patient with mutant load of 33.56%, and of 26% 3 months and 3 years after the onset of LHON, respectively. No m.13513G>A mutation was detected in all his relatives by NGS. Pyrosequencing revealed the mutant load of m.13513G>A mutation of the LHON patient, his mother, father and sister were 22.4%, 1.9%, 0% and 0%, respectively. None of 100 healthy control subjects was detected to harbor m.13513G>A mutation either by NGS or by pyrosequencing of the full mt DNA genome. Conclusions: We first report m.13513G>A mutation with low mutant load presenting as isolated LHON. NGS of the full mitochondrial DNA genome is highly recommended for LHON suspects when targeted PCR amplification for main primary point mutations of LHON was negative. Keywords: Leber's hereditary optic neuropathy; mitochondrial DNA; gene mutation; m.13513G>A.